Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10522-015-9581-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NKp30, NKp46 and DNAM-1 activating receptors on resting and IL-2 activated NK cells from healthy donors according to CMV-serostatus and age

Abstract: Human natural killer (NK) cells are innate lymphoid cells with capacity to kill tumor cells and virus-infected cells. According to the expression of CD56 and CD16 several NK cell subsets have been identified, a major CD56dimCD16+ subpopulation characterized by higher cytotoxic capacity, two CD56bright subsets (CD16-and CD16+) that represent different maturation stages and the fourth CD56-CD16+ subset that correspond to activated dysfunctional NK cells. Previous studies have shown quantitative changes in the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Thus, whereas different studies have shown an age-associated increased expression of KIR (20, 62) and a decreased expression of NKG2A (20), others have not found significant differences in the expression of KIR or NKG2A in the elderly (14, 17, 18, 30) or even a decreased expression of KIR (CD158a) in middle age donors if they are CMV-seropositive (63). The expression of another inhibitory receptor KLRG-1 is significantly reduced with aging (21) and with CMV seropositivity in the young individuals (63).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, whereas different studies have shown an age-associated increased expression of KIR (20, 62) and a decreased expression of NKG2A (20), others have not found significant differences in the expression of KIR or NKG2A in the elderly (14, 17, 18, 30) or even a decreased expression of KIR (CD158a) in middle age donors if they are CMV-seropositive (63). The expression of another inhibitory receptor KLRG-1 is significantly reduced with aging (21) and with CMV seropositivity in the young individuals (63).…”
Section: Discussionmentioning
confidence: 94%
“…The expansion of CD57 + CD56 dim NK cells support previous data showing that acute and latent CMV infection leads to the expansion of CD57 + CD56 dim NK cells that also express NKG2C + (28, 4954). CMV seropositivity is also associated with a decreased expression of other NK receptors, in some cases, as a consequence of the shift of NK cells to the more differentiated NKG2C + CD57 + phenotype (14, 27, 30, 54). These cells have some characteristics of adaptive immunity and are considered “memory” or “adaptive” NK cells (5558).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several original research articles included in this special issue present different aspects of the activity of antioxidants or bioactive compounds in blood (Jansen et al 2015;Capeleto et al 2015), the gender importance in fat accumulation during ageing (Castillo et al 2015), and the importance of the immune system during ageing (Campos et al 2015;Di Benedetto et al 2015).…”
mentioning
confidence: 99%
“…Two papers included in this issue show different aspects of the evolution of the immune system during ageing. Rafael Solana's group from Córdoba, Spain, studies the expression of different natural killer (NK) activating receptors in the different NK cell subsets in order to understand the deterioration of these cells during ageing (Campos et al 2015). Graham Pawelec's group from Tübingen, Germany, discusses the impact of age, sex and CMV-infection on T cells (Di Benedetto et al 2015).…”
mentioning
confidence: 99%